Adaptation and validation of a social support scale in people who suffered COVID-19 - Correa Alvarado, Nancy (2023)
Objective: to adapt the Perceived Social Support (MOS) scale to the pandemic context generated by the COVID19, which was used in its Spanish version for data collection. Methodology: quantitative, cross-sectional, psychometric approach. The sample was composed of 1,039 people over 18 years of age from the Peruvian coast and highlands who suffered from COVID-19. The 46.6% were between 18 and 29 years of age (M: 24 - SD: 1,172) and 54.3% were female. Results: construct validity was achieved through AFC with an adequate two-dimensional model (CFI= .999; TLI= .998; RMSEA= .078; SRMR= .008), likewise, it obtained a high level of reliability with values higher than (ω= 0.8) in its two factors Informational Support and Affective Support. Conclusions: the study concluded that the adaptation of the MOS Perceived Social Support scale with a two-dimensional model is a valid and reliable instrument for people who suffered COVID 19 and is useful for use in Peruvian population suffering situations of social distancing as a result of suffering some disease. Likewise, it is a short instrument that is easy to apply and can be used in large populations.